(untitled) (Journal of Science Foundation, 2016)
Background:Detection ofabnormalities ofaxillary lymph nodes is important for the diagnosis of different pathologies. Objective:The purpose of this present study was to see the accuracy of conventional USG for the differential diagnosis of axillary lymph nodes. Methodology: This cross sectional study was carried out in the Department of Radiology & Imaging at Bangabandhu Sheikh Mujib Medical University, Dhakafrom July 2012 to June 2013 for a period of one year. In this study normal healthy woman who came for screening of breast disease without any symptoms and did not have any abnormality on USG was included and werecategorized as normal patient. Axillary lymph nodes from the normal patients werecategorized as benign lymph nodes. Patients, who came with the complaints of mastalgia with normal breast findings, were included as patients with mastalgia. The lymph nodes from the patients of mastalgia were considered as reactive lymph nodes and patients with known breast cancer and lymph node metastasis were included as malignant patients. Metastatic lymph nodes from breast cancer patients was included diagnosed by cytopathology or histopathology as metastatic lymph nodes. Following patients second visit or final diagnosis the patients were included in the data set. Long axis diameter was taken as longest diameter in long axis. Result: In benign vs reactive lymph node the area under curve for long axis diameter was 0.534 (asymptotic significance 0.307), short axis diameter was 0.589 (asymptotic significance 0.007), sinus length 0.492 (asymptotic significance 0.798), cortical thickness was 0.684 (asymptotic significance 0.0001) short long ratio was 0.570 (asymptotic significance 0.033). In reactive vs metastatic the area under curve for long axis diameter was 0.464 (asymptotic significance 0.391), short axis diameter was 0.741 (asymptotic significance 0.000), sinus length 0.257 (asymptotic significance 0.037), cortical thickness was 0.625 (asymptotic significance 0.003) short long ratio was 0.791 (asymptotic significance 0.000), sinus long ratio 0.279 (asymptotic significance 0.040) cortex short axis ratio .516 (asymptotic significance 0.708).The cut off for short-long axis diameter ratio was 0.43, for short axis was 0.66cm and for cortical thickness 0.37cm. In benign vs metastasis lymph node the area under curve for long axis diameter was 0.533 (asymptotic significance 0.417), short axis diameter was 0.797 (asymptotic significance 0.000), sinus length 0.254 (asymptotic significance 0.000), cortical thickness was 0.757 (asymptotic significance 0.0001) short long ratio was 0.847 (asymptotic significance 0.0001), sinus long ratio 0.241 (asymptotic significance 0.0001) cortex short axis ratio .661 (asymptotic significance 0.0001). Conclusion: To differentiate benign, reactive and metastatic lymph node, cortical thickness and shape are the important parameters. Journal of Science Foundation 2015;13(2):36-45 DOI: http://dx.doi.org/10.3329/jsf.v13i2.27933